Reducing water hammer effect using a surge tank - Rosmaslia Mahide, 1994- 611616 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2017